Elucidating the structural redox behaviors of nanostructured expanded graphite anodes toward fast-charging and high-performance lithium-ion batteries. (30th April 2021) - Son, Dong-Kyu; Kim, Jisu; Raj, Michael Ruby; Lee, Gibaek
Abstract: In this study, the systematic thermal exfoliation of expandable graphite was investigated to determine the optimum temperature for high volume of expansion and to enlarge the interlayer spacing distance ( d- spacing) of expanded graphite (EG). The structural redox behaviors of nanostructured EGs as high-rate anodes for Li-ion storage were thoroughly investigated using various analyses, including an analysis of the electrochemical Li-ion de/intercalation kinetics (structure-dependent Li-ion transport properties) in lithium-ion batteries (LIBs). According to SEM and XRD analyses, all the EG samples exhibit a worm-like morphology containing honeycomb-like micro-pores, and highly crystalline structure with a shrinkage in the d- spacing. Interestingly, EG that is heat-treated for 30 min (EG30) exhibits the largest shrinkage with a d- spacing of 3.37 Å and a crystallite size of 20.96 nm at the optimal thermal exfoliation temperature of 600 °C while retaining analogous long-range-ordered graphitic layers/sheets. Moreover, EG30 exhibited excellent performance in LIBs, with an extremely high average reversible specific capacity of ∼338 mAh g −1 at a current density of 100 mA g −1, a high rate capability of ∼112 mAh g −1 even at an ultra-high rate of 3 A g −1, and a Coulombic efficiency of approximately 100%. The results obtained herein demonstrate that subtle changes in the thermal exfoliation time significantly affect both the honeycomb-like microstructure and Li-ion reversible de/intercalation kinetics of the EG samples, which leading to entirely different staged phase transitions. The shrinkage in the d- spacing of EG as well as crystallite orientation by thermal exfoliation provide new insights for the design and development of EG, which can be exploited to produce competitive EGs for LIBs that power electric vehicles (EVs) and portable electronic devices. Graphical abstract: Image 1 Highlights: Developed expandable graphites (EGs) by optimal thermal exfoliation process. Elucidated their structural redox behaviors as anodes for Li-ion batteries. EG that is heat-treated for 30 min (EG30) exhibits the shrinkage in the d -spacing. EG30 displays stage I-IV & VIII transition phenomena in Li-ion insertion process. EG30 exhibits high reversible capacity (338 mAh g −1 ) and excellent cyclic stability.